Retail Customer Service in the Credit Process at the Pre-Contract Stage - Nowak, Katarzyna (Journal of Finance and Financial Law, 2018)
The conditions to take the right credit decision forms not only price, but also support of the bank. Fairly and properly carried out customer credit process is in the interest of the lender and borrower. It can protect both parties of the loan agreement before negative consequences. Consumer against over-indebtedness and financial troubles, and the bank against troubles of loan repayment. Quality of service is particularly import for the weaker party of the contract – the retail client. The aim of the article is to evaluate the banks practice in terms of retail customer service at the pre-contract stage in the credit process. The article analyses the quality and reliability of the retail customer service and implementation obligations at the major banks in 2017. The conclusions of the studies indicate numerous irregularities in the course of handling clients attributable to banks. The conclusions contained in the article confirm that banks in the credit process do not take in account consumer interests to a sufficient degree and not fulfill of all pre-contract obligations.